Corpus Callosum Index: A practical method for long-term follow-up in multiple sclerosis Índice de corpo caloso: um instrumento prático para o seguimento a longo prazo de pacientes com esclerose múltipla - Fernando Faria Andrade Figueira; Valeria Silva dos Santos; Gustavo Medeiros Andrade Figueira; Ângela Correa Marques da Silva (Arquivos de Neuro-Psiquiatria)
Rather than acute inflammation, long-standing multiple sclerosis (MS) course is hallmarked by relentless axonal loss and brain atrophy, both with subtle clinical expression and scarcely visible on conventional MRI studies. Brain atrophy imaging has sophisticated methodological requirements, not always practical and accessible to most centers. Corpus callosum (CC) is a major inter-hemispheric white matter bundle, grossly affected by long term MS and easily assessed by MRI. To determine whether a practical imaging method can reliably follow presumed axonal loss in patients with progressive MS, we designed a 5-year prospective open label study, enrolling 128 consecutive patients (75 relapsing-remitting (RR) and 53 secondary-progressive (SP)), on regular immunomodulatory therapy compared to control group, formed by 23 patients with MRI considered normal. On a conventional best mid-saggital T1W, CC index (CCI) was obtained by measuring anterior, medium and posterior segments of CC, normalized to its greatest anteroposterior diameter using an orthogonal semi-automated linear system. CCI was measured at baseline and at least once yearly. Results were plotted intra-individually; baseline values were used as reference. At baseline, CCI was able to distinguish SP patients from RR and controls, and on follow-up, despite some overlap, demonstrated a progressive reduction from baseline on both RR and SP groups compared to controls. From the third year on, difference between SP and RR patients reached statistical significance, which did not correlated with disability measured by EDSS. So, a corpus callosum index proved practical and feasible to longitudinally demonstrate morphometric callosal changes with potential to be used as a tool for long-term follow-up, mostly in SP patients. Mais do que inflamação aguda, a perda celular e conseqüente atrofia cerebral são os fatos patofisiológicos mais marcantes na fase progressiva da esclerose múltipla (EM). No entanto, correlatos clínicos e de imagem por ressonância magnética (IRM) destes eventos, requerem sofisticada tecnologia, nem sempre prática e quase nunca acessível à maioria dos centros de tratamento. Deste modo, considerando a hipótese de que esta perda celular compromete fibras associativas que compõem o corpo caloso (CC), estrutura facilmente acessível à IRM convencional, nosso grupo elaborou um estudo prospectivo aberto, atualmente com 5 anos de duração, e envolvendo 128 pacientes consecutivos, todos em acompanhamento regular em nosso centro de tratamento para a EM. A aquisição do índice de CC se deu através de um "melhor" corte meio-sagital em estudo convencional de imagem ponderada por T1, utilizando um sistema linear ortogonal semi-automatizado. Este índice foi obtido no início do seguimento e sua evolução foi acompanhada anualmente. A partir do terceiro ano deste seguimento, sua diferença entre os pacientes com a forma surto-remissiva e aqueles com a forma secundariamente progressiva alcançou significância estatística. Esta diferença não mostrou correlação com o grau de incapacidade medido pelo EDSS. Assim, um índice de CC mostrou-se uma medida prática para o seguimento de alterações morfométricas do corpo caloso, provando assim potencial para ser utilizado no acompanhamento em longo prazo de pacientes com EM, em especial aqueles com a forma progressiva.